Tecnología digital y ocio universitario: Explorando el acceso, uso y actitud de los estudiantes / Digital technology and University leisure: Exploring learner access, use and attitudes - Estefanía de los Dolores Gil-García; Pedro Francisco Alemán-Ramos; Juan Carlos Martín-Quintana (Grupo de Investigación "Nodo Educativo" / Red Universitaria de Tecnología Educativa (RUTE), 2023)
Digital leisure has become a useful and motivating didactic tool for student learning, which also contributes to the acquisition of digital skills. The aim of this study is to analyse the access and use of digital technology by university students at the Universidad de San Carlos de Guatemala (USAC), as well as their attitudes towards digital leisure. This study is framed within the quantitative paradigm, with a non-experimental, cross-sectional, descriptive, exploratory, and correlational design. A total of 203 university students (47.5% male; 52.5% female) from USAC between the ages of 17 and 49 (M=23.33; SD=5.55) participated in the study. The results indicate that the most accessed digital devices and services by university students are smartphones (91.8%) and laptops (80.3%). Additionally, 96% of the students have profiles on social networks. Specifically, younger students (17-20 years) are the ones who have the highest usage of digital technology for leisure purposes and show greater enjoyment of these digital activities. This data shows how university students, particularly newly admitted ones, are highly familiar with digital technology and possess a positive attitude towards digital leisure. Thus, teachers can make use of this openness towards technology and include it as a learning tool in the classroom to then promote digital competences and so create a motivating and effective learning environment.